Harvest of Salmon across Commercial, Subsistence, Personal Use, and Sport Fish sectors, Alaska, 1995-2016 - Jeanette Clark; Alaska Department of Fish and Game (Knowledge Network for Biocomplexity)
This data represents harvest of salmon in Alaska across the commercial, subsistence, personal use, and sport fish sectors. Each of these harvest sectors has a distinct permitting system governed by different departments within the Alaska Department of Fish and Game (ADFG). Commercial harvest is regulated under the Commercial Entry Fishery Commission (CFEC), and refers to the harvest of fish for the purposes of selling them to another party. Subsistence harvest is regulated under the ADFG Subsistence Division, and refers to the harvest of fish for customary and traditional use. Whether use of a stock of fish is considered a "customary and traditional" use is determined by several factors, including length and consistency of use, seasonality, methods and means of harvest, geographic areas, means of handling, preparing, preserving, and storing, intergenerational transmission of knowledge and skills, distribution and exchange, and diversity of resources in an area. Personal use harvest is also governed by the ADFG Subsistence Division. The personal use fishery was created in response to the enactment of the state's subsistence priority law, which precluded some individuals from participating in customary and traditional subsistence fisheries because the stocks they fish are not classified as customary and traditional use stocks. Because the gear associated with the personal use fishery is distinct from the gear typically associated with the sport fishery, the personal use fishery was kept distinct from the sport fishery to prevent confusion amongst the public. More information on the personal use fishery can be found in the Alaska state regulations, Chapter 77 "Personal Use Fishery, Article 1” (5 AAC 77.001). Sport fish harvest is regulated under the ADFG Division of Sport Fish, and refers to the taking of or attempting to take for personal consumption, and not for sale or barter, a fish by hook and line either held in the hand or closely attended. These data are derived from four source datasets: Subsistence and Personal Use Harvest - https://knb.ecoinformatics.org/#view/urn:uuid:7e4586c0-9812-4355-8f3b-1445b9a8ca53 Commercial Harvest (CFEC) - https://knb.ecoinformatics.org/#view/urn:uuid:40473bde-9774-4581-aafb-5d2c3b4a70d1 Commercial Harvest(ADFG Annual Management Reports) - https://knb.ecoinformatics.org/#view/urn:uuid:31b421f3-c48c-473a-bc20-601c738b3a3c Sportfish Harvest - https://knb.ecoinformatics.org/#view/urn:uuid:6a6a530f-3660-424f-adab-c771d1c89a5d) The included .Rmd file sources files from these datasets, aggregates over regions to obtain total harvest by species and region, and merges data from all of the sectors into a single file (Harvest_All_Sectors.csv). The .Rmd file also creates basic plots of harvest by sector by region.